Implementation of 30° Head Up Position Setting in an Effort to Accelerate Recovery in General Post-Anesthesia Patients - Eldiana, Rizka; Lintang Suryani, Roro; Hanum Nur Adriyani, Fauziah (Jurnal Multidisiplin Indonesia, 2024)
Anesthesia is required in surgery to overcome pain and induce loss of consciousness. As many as 80% of patients who undergo surgery use general anesthesia (Siregar et al., 2023). Restoration of consciousness after general anesthesia can cause physiological stress, so careful monitoring is essential (Olfah et al., 2019). A delay in consciousness within 30-60 minutes after general anesthesia is called delayed awakening, which can involve hypoactive consciousness and awakening with delirium (Cascella et al., 2020). One of the interventions to accelerate the recovery of consciousness is to implement a 30° head up position to accelerate recovery. The purpose of Community Service regarding the implementation of the 30° head up position can be carried out to accelerate recovery and see the characteristics of postoperative patients at the Jatiwinangun Purwokerto Surgical Special Hospital. The first monitoring carried out was data collection, patient preparation, implementation, monitoring and evaluation This method was carried out to 30 participants by positioning the patient's head 300 times higher than the bed. then given the position for 15 minutes and then measured the recovery assessment score using the Aldrete score. The general criteria assessed were Motor, respiration, circulation, consciousness, and saturation. The conclusion of the implementation of head up 300 is able to accelerate the recovery period of patients after general anesthesia at the Jatiwinangun Surgical Hospital Purwokerto in 2024. The output of this Community Service is in the form of a journal.